Answer:(gf)(3)=g(3)f(3) g(a)=3a+2 or g(3)=3(3)+2=9+2 =11 f(a)=2a−4 f(3)=2(3)−4=6−4=2 g(3)f(3)=112. Answer
Step-by-step explanation:
Answer:
C and D
Step-by-step explanation:
5^3 - 5^0 = 125 - 1 = 124, so it's not A
5^12 / 5^4 = 5^(12-4) = 5^8, so it's not B
5^7 * 5^-4 = 5^(7+(-4)) = 5^3, so it can be C
5^0 * 5^3 = 5^(0+3) = 5^3, so it can be D
5 + 5^2 = 5 + 25 = 30, so it can't be E
Answer:
how this helps
Step-by-step explanation:
Answer:
<h3>200201+1918191=9191919289+</h3>
Step-by-step explanation:
<h3>tnks </h3>
Answer:
$54.20
Step-by-step explanation:
minute=m
total monthly cost = p
39.99 + .49m = p
39.99 + .49(29) =p
39.99 + 14.21 =p
54.2 =p